External Beam Radiation and Brachytherapy for Prostate Cancer: Is It a Possible Trigger of Large Cell Neuroendocrine Carcinoma of the Urinary Bladder? - Ali Zakaria; Bayan Al Share; Sri Kollepara; Cynthia Vakhariya (Case Reports in Oncological Medicine)
Neuroendocrine tumors commonly involve the respiratory and gastrointestinal systems. Primary genitourinary neuroendocrine tumors are rare, accounting for less than 1% of all bladder carcinomas. Four histopathologic subtypes have been described. Among those, large cell neuroendocrine carcinoma (LCNEC) is the least common, is more aggressive, and generally presents in an advanced stage with poor prognosis compared to transitional cell bladder carcinoma. There is no standardized treatment regimen because of the rarity of the disease. Herein, we present a case of 72-year-old male patient with previously treated prostate cancer, who received external beam radiation therapy and high dose brachytherapy, presenting with intermittent hematuria. Cystoscopy and transurethral resection of bladder tumor (TURBT) were performed. The histopathology and immunohistochemistry were consistent with large cell neuroendocrine carcinoma (LCNEC). Further studies are required to proof the higher risk of neuroendocrine carcinoma of the bladder in patients treated with external beam radiation therapy and brachytherapy for prostate cancer.